Strategi Pengembangan Dan Perluasan Wilayah Pasar Petani Pisang Uli (Musa paradisiaca sapientum) - ramdani, Doni; Yoesdiarti, Arti; Miftah, Himmatul (Universitas Djuanda, 2023)
The study aims to determine the internal and external factors that influence the development of the Banana (Musa paradisiaca sapientum) farming business in Ruguk Village and to formulate an optimal strategy for developing the banana farming business. The analysis used is descriptive analysis, IFE Matrix analysis, EFE Matrix, Internal – External (IE) Matrix, SWOT Diagram, and SWOT analysis. Respondents were selected purposively. The respondents were 8 (eight) experts in their fields. From the results of In the Internal – External (IE) matrix analysis, it was concluded that the farming business should implement a growth strategy, and from SWOT Diagram Analysis since the farming is in quadrant I, they should use an aggressive strategy. Ten specific strategies have resulted from the SWOT analysis, namely the SO strategy: 1). Expanding the scale of banana production, 2) Expanding marketing to supermarkets, and 3) Diversifying processed chip products. WO strategy: 1) Improving the management and the functions of farmer producers cooperative, 2) Providing facilitation and education on diversification of processed products, 3) Utilizing information technology for marketing, communication, and transaction facilities. ST strategy: 1) Improving cultivation management and maintenance to increase the quality and quantity of production. WT strategy: 1) Education on how to handle the disease, 2) Carry out plant maintenance regularly, and 3) Delivery on time.